2019
DOI: 10.1534/g3.118.200810
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Transcriptional Profiling of the Gastrointestinal Tract of Ruminants from Birth to Adulthood Reveals Strong Developmental Stage Specific Gene Expression

Abstract: One of the most significant physiological challenges to neonatal and juvenile ruminants is the development and establishment of the rumen. Using a subset of RNA-Seq data from our high-resolution atlas of gene expression in sheep ( Ovis aries ) we have provided the first comprehensive characterization of transcription of the entire gastrointestinal (GI) tract during the transition from pre-ruminant to ruminant. The dataset comprises 164 tissue samples from sheep at four different time poi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 75 publications
(140 reference statements)
2
21
0
Order By: Relevance
“…Throughout the GI tract, there was a strong immune signature, similar to that observed in neonatal and adult sheep (Bush et al, 2019), which was greatest in clusters 10 and 19 ( Table 3 ) where expression was high in the ileum and Peyer’s patches, thymus, and spleen. Cluster 10 had a more general immune related profile with higher expression in the spleen and significant GO terms associated with cytokine receptor activity (p = 1.3x10 -8 ) and T-cell receptor complex (p = 0.00895).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Throughout the GI tract, there was a strong immune signature, similar to that observed in neonatal and adult sheep (Bush et al, 2019), which was greatest in clusters 10 and 19 ( Table 3 ) where expression was high in the ileum and Peyer’s patches, thymus, and spleen. Cluster 10 had a more general immune related profile with higher expression in the spleen and significant GO terms associated with cytokine receptor activity (p = 1.3x10 -8 ) and T-cell receptor complex (p = 0.00895).…”
Section: Resultssupporting
confidence: 57%
“…Even at this early stage of development, the typical epithelial signature of the rumen (Xiang et al, 2016a; Xiang et al, 2016b) was observed. Genes coexpressed in the rumen (clusters 7 and 13 – Table 3 ) were typical of a developing rumen epithelial signature (Bush et al, 2019) and were associated with GO terms for epidermis development (p = 0.00016), keratinocyte differentiation (p = 1.5x10 -14 ), and skin morphogenesis (p = 8.2x10 -6 ). Large colon (cluster 12) included several genes associated with GO terms for microvillus organization (p = 1x10 6 ) and microvillus (p = 6.3x10 6 ) including MYO7B which is found in the brush border cells of epithelial microvilli in the large intestine.…”
Section: Resultsmentioning
confidence: 99%
“…Although ruminant species have anatomically equivalent gastrointestinal tracts, we considered that GI tract gene expression may differ due to differences in diet, metabolism, or habitat. To test this hypothesis, we compared gene expression in the GI tract between buffalo and sheep, using gene expression data from the sheep atlas (Clark et al, 2017), which have also been the focus of a separate analysis (Bush et al, 2018). Equivalent datasets from both species were clustered using Graphia Professional with genes expressed in the forestomach and small and large intestines compared between species.…”
Section: Resultsmentioning
confidence: 99%
“…The new transcript models created (732 protein-coding transcripts, representing 631 genes, plus 6,756 lncRNAs) were then integrated with the “second pass” Kallisto index to create a “third pass” index, with expression quantification repeated as above. Transcript models were retained only if they could be robustly annotated, using the criteria described in Clark et al (2017) for protein-coding genes, and the criteria described in Bush et al (2018) for lncRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…We chose to focus this analysis on immune-related tissues in part because of the depth of available sequence in those tissues, and in part because they contain abundant immune cell populations. The diversity of cell populations is reflected in the transcriptional complexity of immune tissues and cell types in the sheep gene expression atlas data set (Clark et al, 2017; Bush et al, 2019). As such, this subset of tissues gave us a transcriptionally rich data set in which to measure ASE.…”
Section: Introductionmentioning
confidence: 99%